Low-Grade Fibromyxoid Sarcoma of the Lateral Skull Base: Presentation of Two Cases - Evgenia Chetverikova; Priit Kasenõmm (Case Reports in Otolaryngology)
Low-grade fibromyxoid sarcoma (LGFMS) is a rare slow-growing malignant tumour with a deceptively benign histologic appearance. Herein, we report two cases of LGFMS with variable clinical presentations. The first case was a 17-year-old female who referred to our department due to deaf ear on the right together with ipsilateral gag reflex impairment and globus sensation in the pharynx. The second case was a 35-year-old female with recurrent LGFMS, suffering from headaches, vertigo, and episodes of loss of consciousness. LGFMS of the temporal bone is a rare pathology, and to the best of our knowledge, no such cases have been reported before.